Protective effects of zinc on oxidative stress enzymes in liver of protein deficient rats Efectos del Zinc sobre enzimas de estrés oxidativo de ratas con déficit proteico - P. Sidhu; M. L. Garg; D. K. Dhawan (Nutrición Hospitalaria, 2004)
This study was designed to evaluate the protective effects of zinc on the liver activities of antioxidant enzymes in protein-deficient rats. Zinc sulfate at a dose level of 227 mg/l in drinking water was administrated to Sprague Dawley normal control as well as to protein-deficient rats for a total duration of eight weeks. The effects of zinc treatment and protein deficiency alone as well as combined were studied on rat liver antioxidant enzymes which included catalase, glutathione peroxidase (GPX), glutathione reductase (GR), superoxide dismutase (SOD), and glutathione S-transferase (GST). Protein deficiency in normal rats resulted in a significant increase in hepatic lipid peroxidation and in catalase, Gpx, GR and GST activity. A significant inhibition in the levels of SOD activity and reduced glutathione (GSH) was observed following protein deficiency in normal rats. Zn treatment to protein deficient animals lowered lipid peroxidation and catalase, Gpx and GST activities, and also resulted in a significant elevation in the levels of GSH and SOD activity. The concentration of zinc decreased significantly in protein deficient animals but returned to normal levels when zinc was administered. Este estudio fue diseñado para estudiar los efectos protectores del zinc sobre la actividad de los enzimas antioxidantes del hígado en ratas con déficit proteico. Se administró sulfato de zinc en una dosis de 227 mg por litro en agua a ratas Sprage Dawley control y a un grupo de ratas con déficit proteico durante un período de ocho semanas. Los efectos del tratamiento de zinc y de la deficiencia proteica per se, así como su combinación, fueron estudiados sobre los encimas antioxidantes de¡ hígado de la rata, incluyendo catalasa, glutation peroxidasa (GPX), glutation reductasa (GR), superóxido dismutasa (SOD) y glutation s-transferasa (GST). La deficiencia protéica en ratas normales produjo un aumento significativo en la peroxidación lipídica del hígado, así como en la actividad de catalasa GPX, GR y GST. Hubo una inhibición significativa de los niveles de actividad SOD y una reducción del glutation en las ratas con déficit proteico. El tratamiento con zinc a los animales con déficit proteico disminuyó la peroxidación lipídica y la actividad de catalasa GPX y GST, y también produjo una elevación significativa en los niveles de actividad de GSH y SOD. La concentración de zinc disminuyó de manera significativa en los animales con déficit proteico, pero volvió a los niveles normales cuando se administró zinc.